The Performance Puzzle: Unlocking Public Sector Excellence in Thailand’s Administrative Reform - Zhang , Anran; Ma , Haoyu; Zhao , Shuo; Qian , Pengjun; Chen , Jianwu (International Journal of Accounting and Economics Studies, 2025)
Job satisfaction and organizational commitment are factors that mediate this relationship. Drawing on a sample of 452 employees from central administrative units, the study uses Social Exchange Theory and the Job Demands-Resources model to explore these processes. The results suggest that work factors are an important predictor of job performance. The results revealed that work-related factors significantly and heavily influence job performance. Job satisfaction and organizational commitment completely mediated the effect here. In relation to the study variables, of the work-related factors, leadership and work environment, particularly, could explain to a greater extent. The results contribute some theoretical and practical implications for public sector performance in Thailand.